2022
DOI: 10.3390/pharmaceutics14051003
|View full text |Cite
|
Sign up to set email alerts
|

Novel Luteolin-Loaded Chitosan Decorated Nanoparticles for Brain-Targeting Delivery in a Sporadic Alzheimer’s Disease Mouse Model: Focus on Antioxidant, Anti-Inflammatory, and Amyloidogenic Pathways

Abstract: Preparation and evaluation of a non-invasive intranasal luteolin delivery for the management of cognitive dysfunction in Alzheimer’s disease (AD) using novel chitosan decorated nanoparticles. Development of luteolin-loaded chitosomes was followed by full in vitro characterization. In vivo efficacy was evaluated using a sporadic Alzheimer’s disease (SAD) animal model via intracerebroventricular injection of 3 mg/kg streptozotocin (ICV-STZ). Treatment groups of luteolin suspension and chitosomes (50 mg/kg) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 93 publications
2
28
0
Order By: Relevance
“…Cs and its derivatives are successfully used as a liposome shell for drug delivery through the mucous membranes of the nose [36], eyes [37], mouth [38], and digestive system [39]. Cs can interact with negatively charged fragments, mainly with sialic acid in the mucous layers, due to its positively charged amino groups [40]. The mucoadhesive property of Cs is associated with the penetration of the polymer into glycoprotein mucin chains and the formation of tangles with mucus.…”
Section: Introductionmentioning
confidence: 99%
“…Cs and its derivatives are successfully used as a liposome shell for drug delivery through the mucous membranes of the nose [36], eyes [37], mouth [38], and digestive system [39]. Cs can interact with negatively charged fragments, mainly with sialic acid in the mucous layers, due to its positively charged amino groups [40]. The mucoadhesive property of Cs is associated with the penetration of the polymer into glycoprotein mucin chains and the formation of tangles with mucus.…”
Section: Introductionmentioning
confidence: 99%
“…Our prepared formulation as well as QRC dispersion demonstrated no signs of nasal irritation when administered intranasally compared to when saline was administered intranasally. Based on these observations, both QRC loaded polymeric nanocapsules as well as QRC dispersion in the no irritation level on the nasal mucosa irritation index indicating that both are cilio-friendly [24]. To further validate the safety of our chosen formula, histopathological examination was conducted to analyze the rats' mucosa when the rats received either saline, benzalkonium chloride, or the chosen formula.…”
Section: Discussionmentioning
confidence: 95%
“…During nasal administration conducted in animal studies, an observational nasal irritation test was conducted [24]. Visual observation was conducted when saline, QRC dispersion, and QRC loaded polymeric nanocapsules were administered intranasally.…”
Section: Observational Nasal Irritation Testmentioning
confidence: 99%
“…All over the LUT-CHS reduced, the Aβ aggregation in brain of sporadic AD mouse. This suggested that the nanodrug delivery system with LUT-CHS is neuroprotective and safe with non-invasive drug administration (Abbas et al, 2022).…”
Section: Luteolinmentioning
confidence: 96%